Improving the Teachers Skills in Semarang City and Surrounding Areas in Using PhET Simulations Application-Based Virtual Laboratories - Istikomah, Istikomah; Arsini, Arsini; Saputri, Affa Ardhi; Jasuri, Jasuri; Susilawati, Susilawati; Fariyani, Qisthi; Herseptianingrum, Rida (LP2M of Institute for Research and Community Services - UIN Walisongo, 2023)
The practicum learning process transformed from offline to online during the pandemic. Teachers must have the skills to use virtual laboratory applications to improve the learning process. Community service activities have been carried out in the form of virtual laboratory training to improve the skills of junior-senior high school teachers based on the PhET Simulations application in the city of Semarang and surrounding areas. Evaluation of training activities using the self-assessment questionnaire method before and after the participants attended the training. The questionnaire comprises four aspects of ability: the ability to access the virtual practicum application, use the PhET application via a browser, download simulations on the PhET Simulations application, and use the PhET Simulation application as a means of physics practicum. Based on the analysis of the n-gain test, the results of increasing competence were 32% of participants included in the high category, 30% of participants included in the medium category, and 38% of participants included in the low category.